Improving the Life Cycle Energy Performance of Apartment Units through Façade Design. (2017) - Stephan, André; Jensen, Christopher A.; Crawford, Robert H.
Abstract: The construction and operation of buildings require huge amounts of resources and contribute to climate change and resource depletion. In Australia, apartment buildings are increasingly being erected and are typically characterized by fully-glazed façades with a limited understanding of the life cycle implications of such design. This study uses a typical apartment unit in three climates (Melbourne, Australia; Brisbane, Australia; and Dunedin, New Zealand) and tests 87 different façade variations involving a range of window-to-wall ratios, window types and wall types. For each variation, the life cycle energy demand is quantified over 50 years and compared to that of the base case. Results show that the window-to-wall ratio is the most significant parameter and that smaller glazed areas reduce both embodied and operational energy use. Climate and orientation are other significant parameters, modifying the ranking of variations in terms of life cycle energy performance. In addition, the embodied energy of the façade represented, on average, 45% of the apartments' life cycle energy demand, highlighting the importance of material selection. Reducing glazed area, considering a life cycle approach and carefully composing a façade with respect to climate and orientation are therefore critical factors in improving the life cycle energy performance of apartment units.